Design of an Intelligent Fiber Bragg Grating Temperature Measurement System for Electrical Equipment. Issue 2 (April 2021) - Wang, Liting; Han, Hulin
Abstract: For the power system, the main reason for many fire accidents is that the temperature of electrical equipment is too high, and now the widely used fire detector can only detect the fire that has occurred. If the temperature change of electrical equipment can be tracked in real time and the alarm information can be sent in time when the operating temperature is too high, the fire of power system can be scientifically and effectively prevented. The use of fiber Bragg grating sensor can provide a basis for the realization of the theoretical conception. For the traditional temperature measurement system, fiber Bragg grating temperature measurement system has the advantages of convenient maintenance, fault detection, less affected by light source power fluctuation, information sharing and long service time. It can effectively measure the temperature of isolated contact of high-voltage switchgear, the temperature of wet steam inside steam turbine and the surface temperature of power cable, etc. This paper researches a design of fiber Bragg grating temperature measurement system.